Etika Bisnis dalam Perpektif Ekonomi Syari'ah: Implementasi Etika Bisnis Islam Dalam Menjalankan Usaha Kecil di Toko Cahaya Kota Kendal - Muna, Rifatul (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2025)
ABSTRACT This research aims to explain business ethics from an Islamic economic perspective. The author employed a descriptive qualitative research method, drawing data from various books related to the research topic. This research chose a qualitative method because it can yield concrete results regarding existing societal problems. Etymologically, ethics comes from the Greek word ethos, which is synonymous with attitude, a person's way of thinking, habits or customs, morals, and good character. Ethics can also be defined as principles or behaviors that distinguish right from wrong. Ethics is also a branch of philosophy that studies various aspects of life, such as values, norms, rules, and morals. In reality, the Muslim world still faces economic shortages. In this regard, ethics has become the most important reference for all business worlds from an Islamic perspective. In practice, Islamic business ethics can be used as a foundation to guide individuals in Islamic awareness in all their economic activities. Failure to apply ethics in business can destroy their lives, both in this world and the hereafter. Many producers who are aware of their business ethics can demonstrate positive performance. The teachings explain that a businessperson will be successful if they apply Islamic ethics in their business. Ethics has five main principles: Tawhid, Balance, Free Will and Responsibility, and finally, Truth.